Dogs motivate obese children for physical activity: key elements of a motivational theory of animal-assisted interventions - Wohlfarth, Rainer; Mutschler, Bettina; Beetz, Andrea; Kreuser, Friederike; Korsten-Reck, Ulrike (Frontiers in Psychology, 2013)
Background: There is empirical evidence that the presence of a companion animal can have a positive impact on performance. The available evidence can be viewed in terms of differing hypotheses that attempt to explain the mechanisms behind the positive effects. Little attention has been given to motivation as a potential mode of action with regards to human-animal interactions. First we give an overview of evidence that animals might promote motivation. Second we present a study to examine the effect of a therapy dog on exercise performance in children with obesity. Methods: 12 children, aged 8 to 12 years old, were randomly assigned to two groups in a crossover design: dog-group and human confederate group. Several types of physical activities via accelerometer and subjective ratings of wellbeing, satisfaction and motivation were assessed. Data were analyzed using analysis of variance for repeated measures on one factor. Results: The main effect of condition was significant for all performance variables. There was less passive behavior and more physical activity for all performance variables in the presence of the dog than in that of the human confederate. Between dog- and human- condition there was no difference in the subjective rating of motivation, wellbeing or satisfaction. Discussion: The results demonstrate that the presence of a therapy dog has the potential to increase physical activity in obese children. Task performance as a declarative measure was increased by the presence of the dog in comparison to a human confederate, but self-report measures of motivation, satisfaction or wellbeing did not differ between the two conditions. Therefore it stands to reason that a dog could trigger implicit motives which enhance motivation for activity. The results of our study indicate the potentially beneficial effect of incorporating dogs into outpatient training for obese children.